The north-south divide, the euro and the world - Konstantinos Chisiridis; Kostas Mouratidis; Theodore Panagiotidis (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2018)
The European north-south divide has been an issue of a long-standing debate. We employ a Global VAR model for 28 developed and developing countries to examine the interaction between the global trade imbalances and their impact within the euro-area framework. The aim is to assess the propagation mechanisms of real shocks, focusing on the interconnections among the north euro area and the south euro area. We incorporate theory-based long-run restrictions and examine the effects of (i) non-export real output shocks, (ii) expansionary shocks and (iii) real exchange rate shocks. The results provide support for symmetric adjustment in the euro area; an expansionary policy of the north euro area and increased competitiveness in the south euro area can alleviate trade imbalances of the debtor euro area economies. From the south euro area perspective, internal devaluation is the most beneficial policy. North euro area and U.S. origin shocks to domestic output exert a dominant influence in the rest of the Europe and Asia while the strong linkage between trade flows within the euro area is confirmed.
urn:nbn:de:101:1-2019040811174967161963
Keywords: C33; E27; F14; 330; North-South Euro Area Trade Imbalances; Global Trade Imbalances; International Linkages; Global VAR; Spillover Effects